Solve for x (complex solution)
x=\frac{1+i\sqrt{7}}{2}\approx 0.5+1.322875656i
x=\frac{-i\sqrt{7}+1}{2}\approx 0.5-1.322875656i
Graph
Share
Copied to clipboard
\left(-x+\frac{1}{2}\right)^{2}=0.25-2
Subtracting 2 from itself leaves 0.
\left(-x+\frac{1}{2}\right)^{2}=-1.75
Subtract 2 from 0.25.
-x+\frac{1}{2}=\frac{\sqrt{7}i}{2} -x+\frac{1}{2}=-\frac{\sqrt{7}i}{2}
Take the square root of both sides of the equation.
-x+\frac{1}{2}-\frac{1}{2}=\frac{\sqrt{7}i}{2}-\frac{1}{2} -x+\frac{1}{2}-\frac{1}{2}=-\frac{\sqrt{7}i}{2}-\frac{1}{2}
Subtract \frac{1}{2} from both sides of the equation.
-x=\frac{\sqrt{7}i}{2}-\frac{1}{2} -x=-\frac{\sqrt{7}i}{2}-\frac{1}{2}
Subtracting \frac{1}{2} from itself leaves 0.
-x=\frac{-1+\sqrt{7}i}{2}
Subtract \frac{1}{2} from \frac{i\sqrt{7}}{2}.
-x=\frac{-\sqrt{7}i-1}{2}
Subtract \frac{1}{2} from -\frac{i\sqrt{7}}{2}.
\frac{-x}{-1}=\frac{-1+\sqrt{7}i}{-2} \frac{-x}{-1}=\frac{-\sqrt{7}i-1}{-2}
Divide both sides by -1.
x=\frac{-1+\sqrt{7}i}{-2} x=\frac{-\sqrt{7}i-1}{-2}
Dividing by -1 undoes the multiplication by -1.
x=\frac{-\sqrt{7}i+1}{2}
Divide \frac{i\sqrt{7}-1}{2} by -1.
x=\frac{1+\sqrt{7}i}{2}
Divide \frac{-i\sqrt{7}-1}{2} by -1.
x=\frac{-\sqrt{7}i+1}{2} x=\frac{1+\sqrt{7}i}{2}
The equation is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}